Design and fabricate rocket engine - Tg Kamarul Azhan, Tg Kamaruddin (2010)
The objective of this project is to design and fabricate the Rocket Engine.This project describe the shape of Rocket that will fabricate follow the dimension that give by my supervisor.Actually there a several type of Rocket Engine.There are Rocket Engine based of thermal,water,hybrid,solid,and resistojet(electronic).So,the Rocket that will fabricate is from the solid type.One of the important thing a rocket is type of noozle,from the research in the internet De’Laval Noozle is the better type of noozle to use.Then material also another important thing in making Rocket.Material that will use must have good enough strenght to hold the explosion that will happen to move up the rocket.The better material is Stainless Steel it is light and have a good strenght,but cause of limited soucrce the material that use for make this Rocket is from mild steel.It is also have good strenght but it heavy than stainless steel.This project start from making the design and make it using Solid Work Software.Finish the design then the rocket can be made use a Lathe Machnine.Majority this rocket will be made by Lathe Machine.But from the start of fabricte the machine that involve also like bendsaw and drilling machine.Rocket engine that will be made have three part.First part is cap to close the hole on the upper body,a body and noozle.All this part will be assembly and were tied by bolt.It was susessfully done and able to function as needed.